Analisis strategi guru dalam pembelajaran bahasa Indonesia bercerita pada pembelajaran berbasis online di kelas V SD - Maulida Khalifah; Rukayah Rukayah; Joko Daryanto (Universitas Sebelas Maret, 2022)
The aim of this study was to describe the teacher strategy in storytelling skills Indonesia language learning in online based-learning on the 5th grade of SD Ta’mirul Islam Surakarta in the academic year 2020/2021. This research uses descriptive qualitative research methods with a case study approach. Taking research subjects using the Purposive Sampling Technique by conducting interviews, observation, and document studies on the informants. The data source of this study was teacher of grade 5 at SD Ta’mirul Islam Surakarta and six childern as research samples. The results of this study idicate that teacher uses many strategies in storytelling skills Indonesia language learning in online based-learning. There are obstacles faced by teacher and students on that learning.